RUANG PRIVAT INDIVIDU DALAM SISTEM KAWIN MAWIN MASYARAKAT SUMBA TIMUR - Muthmainnah, Lailiy; Trisakti, Sonjoruri Budiani (Jurnal Filsafat "WISDOM", 2010)
AbstractEast Sumba people have strong kinship and marital system.All of the living aspect of the East Sumba people managed by their kabihu. The various rights and duties will be emerge in the kabihu, include of this point is the custom duties related to the marriage process. Marriage in the East Sumba people have great symbol, not only for having a child but also to keep save uma marapu. The kinship of East Sumba people is patriarchy and the marriage system is always exogamy. It is taboo for marriage in one kabihu. Related to the kinship system in East Sumba, when a woman get married with a man from a different kabihu and her husband finishes his duties (belis), the woman will join her husband kabihu. Then, there is no kinship relation again between her and her old kabihu.Consequently, almost of the yera (wife’s family) make belis isimpossible to pay. From material aspect, belis process will give an advantage for the woman’s family but for the couple it will restraint their freedom. There is no private sphere for them because all of their marriage process will be judged and done by their family and kabihu.Keywords: East Sumba, marriage, uma marapu, kabihu, belis, yera,private sphere.